ANALYZING THE RELATIONSHIP AMONG CLINICAL SYMPTOMS, X-RAY RESULTS, AND CARTILAGE WEAR PATTERNS IN KNEE OSTEOARTHRITIS USING T2 MAPPING MRI - CHUNCHESH MD; VANI AHUJA; SUNIL SANTHOSH G; BHARGAV G (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Osteoarthritis (OA) is a condition that causes joint pain, varying degrees of functional limitations, and a decrease in overall quality of life. The purpose of this study was to examine the progression of cartilage degeneration in knees affected by symptomatic OA and determine its relationship with X-ray and T2 map MRI findings. Methods: This study was conducted at a Tertiary Care Teaching Institute in India and involved 40 patients. It was an observational type of study. For our assessment, we utilized the Western Ontario and McMaster University (WOMAC) osteoarthrosis index to evaluate function, quality of life, and joint pain. Medical imaging technique A standing AP view of the affected knee joint was taken using plain radiographs. Once the X-rays were obtained, they were graded using the Kellgren–Lawrence Classification, which ranges from 0 to 4 grades. Results: Out of the total patients, 6.0% were <40 years old, 21.2% were between 41 and 50 years old, 27.2% were between 51 and 60 years old, 39.3% were between 61 and 70 years old, and 6.0% were above 70 years old. In this study, there were 21 females (63.6%) and 12 males (36.4%). In this study, the researchers found that there was no distinction between the sides of the limb affected. Both the left and right sides were involved in 13 cases each, accounting for 39.39% of the total cases. In addition, 7 cases, or 21.21%, reported experiencing bilateral knee pain. Merchant grade reported that out of the knees examined, 17.5% had Grade 0, 45% had Grade 1, 27.5% had Grade 2, 10% had Grade 3, and none had Grade 4. Conclusion: The findings of this study suggest that T2 map MRI has the ability to accurately measure abnormal cartilage changes in conditions that affect the mechanical properties of the knee joint. It is crucial to have non-invasive methods that can assess early cartilage matrix changes. These methods are important for initiating early treatment, monitoring disease progression, planning operative procedures, and following up on operative cartilage repair.